C11orf54 catalyzes L-xylulose formation in human metabolism - Marco Malatesta; Carlo De Rito; Francesca Gasparini; Giovanni Merici; Davide Dell’Accantera; Giacomo Quilici; Francesco Sansone; Riccardo Percudani (Proceedings of the National Academy of Sciences, 2025)
Excretion of L-xylulose is the hallmark of pentosuria, the fourth of Garrod’s inborn errors of metabolism, yet the molecular basis for L-xylulose formation remains unknown. Here, by projecting coevolutionary data for 511,114 orthogroups across 1,929 eukaryotic genomes onto metabolic maps, we screen for unmapped genes in human metabolism. Among these, we show that the DUF1907 domain of C11orf54 catalyzes formation of L-xylulose by establishing a zinc-coordinated Michaelis complex with β-keto-L-gulonate (BKG). The identification of BKG decarboxylase completes the pentose pathway, in which pentose sugars are produced by decarboxylation of nonphosphorylated hexose precursors. The pathway was present in the unicellular ancestor of animals and is conserved in all deuterostomes, in contrast to the alternative L-ascorbate (vitamin C) biosynthesis pathway. An increased flux toward pentoses may have represented an evolutionary tradeoff, favoring energy metabolism and redox cofactor balance at the expense of ascorbate biosynthesis in organisms, such as humans and other Haplorhini primates, where dietary vitamin C intake prevents scurvy.